Mixed Methods Evaluation of a Produce Prescription Program for Pregnant Women. Issue 4 (2nd October 2017) - Trapl, Erika S.; Joshi, Kakul; Taggart, Morgan; Patrick, Alison; Meschkat, Erika; Freedman, Darcy A.
ABSTRACT: Fruit and vegetable consumption has been shown to be associated with positive birth outcomes. Farmers' markets (FMs) are a growing opportunity to increase access in neighborhoods with limited access to fruits and vegetables. The objective of this mixed methods study was to determine the applicability of integrating a produce prescription intervention (PRx) with the existing health care and farmers' market systems in Cuyahoga County, Ohio. The program served pregnant women within underserved areas with limited access to fruits and vegetables. The intervention included nutritional counseling and $40 FM vouchers at monthly prenatal visits. Monthly surveys with participants and voucher redemption logs from FM tracked participant use of PRx vouchers. Interviews with providers at 4 program sites assessed perceived impact of PRx on participants and patient–provider relationship. Of the 75 PRx participants, 56% redeemed at least one voucher, and 95% reported that program materials were relevant and useful. Providers ( n = 10) indicated that PRx created opportunities to talk about diet with participants, greater awareness about FMs, and new shopping habits. The PRx model is an innovative approach to increase access to produce among low-income pregnant women. Future work should aim to increase voucher redemption and examine ways to implement PRx in more prenatal settings.